2020
DOI: 10.3390/su12176907
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fashion Avoidance Beliefs and Anti-Consumption Behaviors: The Cases of Korea and Spain

Abstract: The ethics of the fast fashion industry have been called into question with the emergence of new consumption paradigms, such as anti-consumerism and sustainable consumption. This study aims to explore the conceptual structure of fast fashion avoidance beliefs that have led to the anti-consumption of fast fashion. Data were collected from female consumers aged between 20 and 39 years with experiences of purchasing fast fashion brands in Korea and Spain. The structure of avoidance beliefs was compared through se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 56 publications
(101 reference statements)
1
40
0
2
Order By: Relevance
“…cused on analyzing consumer perspectives on fashion sustainability [33][34][35][36][37][38][39][40][41], since it is extremely important to identify the main causes that drive consumption habits towards or away from sustainable fashion practices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cused on analyzing consumer perspectives on fashion sustainability [33][34][35][36][37][38][39][40][41], since it is extremely important to identify the main causes that drive consumption habits towards or away from sustainable fashion practices.…”
Section: Methodsmentioning
confidence: 99%
“…The fast fashion model has registered declining sales [9]. This is because some consumers avoid these types of brands due to low product quality or unoriginal and massproduced styles, which negatively affect the individuality of the piece and the lack of the brand's social and environmental responsibility [40]. This places fast fashion retailers in the social pressure spotlight [93].…”
Section: Design Andmentioning
confidence: 99%
“…As discussed in Section 3.2.2, although consumption has increased, the number of usages has decreased by 36% compared to just 15 years ago [39]. It is suggested that this reduction in use is not only a result of our temptation to buy new garments but is also a consequence of cheaply made, low-quality garments [64,[98][99][100], which can result in a lack of attachment between product and consumer [31,100].…”
Section: From Quality To Quantitymentioning
confidence: 99%
“…Some studies analyze the relationship/compatibility between luxury fashion and sustainability [39]. While the vast majority argue that luxury fashion companies should be considered sustainable per se [41][42][43], and they have less need for sustainability because they are always representative of slow fashion [38], some people consider luxury fashion and sustainability to be irreconcilable by definition, since luxury implies excess, not to mention production and consumption driven by aspects other than satisfying basic needs [42].…”
Section: Fast Fashion Versus Luxury Fashionmentioning
confidence: 99%
“…The same disparity found amongst consumers can be observed amongst researchers: this is one of the reasons why we wish to address this question in our study. Many authors are skeptical regarding the sustainability efforts of the major fashion retailers [41,43,48]. Fletcher [45] questions the model of continuous growth itself, calling for a vision of the fashion sector based on a different starting point.…”
Section: Fast Fashion Versus Luxury Fashionmentioning
confidence: 99%